The role of extremism in the Indian independence movement: भारतीय स्वतंत्रता आंदोलन में उग्रवाद की भूमिका - Meena, Ramjeelal (RESEARCH HUB International Multidisciplinary Research Journal, 2023)
In the present paper a historical study of the role of extremism in the Indian National Movement has been made. The late nineteenth and early twentieth centuries saw the rise of a new party in the Indian National Congress, which was fiercely critical of the ideals and methods of the old leaders. These angry young people wanted that the aim of the Congress should be Swaraj, which they should achieve with self-confidence and self-reliance. This new party is said to be extremist in comparison to the old moderates. Despite the long efforts of the liberals, basically nothing could be achieved. It is understood that the government has taken the Liberals’ efforts as a sign of weakness. Therefore, leaders like Bankim Chandra Chatterjee, Aurobindo Ghosh, Bal Gangadhar Tilak, criticizing the liberals, spoke of achieving independence through strong pressure. In this phase of the Indian National Movement, militants were launched on the one hand and revolutionary movements on the other. Both were fighting for the sole cause of freedom from the British rule and the attainment of complete independence. On the one hand people of militant ideology were fighting on the basis of boycott movement, on the other hand, people of revolutionary ideology wanted to gain freedom by using bombs and guns. Bal Gangadhar Tilak, Lala Lajpat Rai and Vipin Chandra Pal played an important role in the rise of nationalism in India by extremists. Abstract in Hindi Language: प्रस्तुत पत्र में भारतीय राष्ट्रीय आंदोलन में उग्रवाद की भूमिका का एक ऐतिहासिक अध्ययन किया गया है। उन्नीसवीं और बीसवीं सदी के उत्तरार्ध में भारतीय राष्ट्रीय कांग्रेस में एक नई पार्टी का उदय हुआ, जो पुराने नेताओं के आदर्शों और तरीकों की कट्टर आलोचक थी। ये नाराज तरुण लोग चाहते थे कि कांग्रेस का उद्देश्य स्वराज होना चाहिए, जिसे उन्हें आत्मविश्वास और आत्मनिर्भरता के साथ हासिल करना चाहिए। इस नई पार्टी को पुराने उदारवादियों की तुलना में उग्रवादी कहा जाता है। उदारवादियों के लंबे प्रयासों के बावजूद, मूल रूप में कुछ भी हासिल नहीं किया जा सका। यह समझा जाता है कि सरकार ने उदारवादियों के प्रयासों को कमजोरी का संकेत माना है। इसलिए, बंकिम चंद्र चटर्जी, अरविंद घोष, बाल गंगाधर तिलक जैसे नेताओं ने उदारवादियों की आलोचना करते हुए, मजबूत दबाव के माध्यम से स्वतंत्रता प्राप्त करने की बात कही। भारतीय राष्ट्रीय आंदोलन के इस चरण में, एक तरफ उग्रवादियों को चलाया गया और दूसरी तरफ क्रांतिकारी आंदोलनों को। दोनों एकमात्र उद्देश्य, ब्रिटिश राज्य से मुक्ति और पूर्ण स्वराज्य की प्राप्ति के लिए लड़ रहे थे। एक ओर उग्रवादी विचारधारा के लोग बहिष्कार आंदोलन के आधार पर लड़ रहे थे, दूसरी ओर, क्रांतिकारी विचारधारा के लोग बम और बंदूकों के इस्तेमाल से आजादी हासिल करना चाहते थे। बाल गंगाधर तिलक, लाला लाजपत राय और विपिन चंद्र पाल ने भारत में उग्रवादियों ने राष्ट्रवाद के उदय में महत्वपूर्ण भूमिका निभाई। Keywords: उग्रवादियों का उदय, अतिवाद के कारण, लाजपत राय का कथन, भारतीय राष्ट्रीय आंदोलन में उग्रवाद के उदय और उग्रवादियों की भूमिका।